Pemberian Jus Buah Nanas Terhadap Penurunan Kadar Asam Urat Pra Lansia - Rahayu, Rahayu; Arsi, Ranida; Wulandari, Ria; Utama Saputra, Andre (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Gout Arthritis is a type of arthritis that occurs due to the accumulation of uric acid crystals. This condition can occur in any joint, such as in the toes, ankles, knees, and most often in the big toe. The prevalence of gout sufferers in the world according to WHO reached 34.2% in 2029 and increased in 2020. This is very important because gout will cause severe pain and will interfere with comfort, especially in the pre-elderly which can reduce their quality of life. This study aims to determine the effect of giving pineapple juice on reducing uric acid levels. This type of research is quantitative with a quasi-experimental design using a one group pretest-posttest design. The tools used are easy touch to measure uric acid levels, and observation sheets. The population in this study was 38 people, then using the Slovin formula, a sample of 17 people was obtained. Samples were taken using the purposive sampling technique. The study was conducted at the Ngulak Banyuasin Health Center in July 2024. The results obtained were that the uric acid level before being given Pineapple Juice was 9.5 mg/dl and the uric acid level after being given pineapple juice decreased to 5.5 mg/dl. Pineapple juice was given once a day at noon after lunch for 5 days. Uric acid levels were measured before administration on the first day and after administration of pineapple juice on the fifth day. The results of the statistical test using the Parried T-Test showed that the significance value was p-value 0.000 (p<0.05) which means that there is a significant effect between pineapple juice and reducing uric acid levels. It is hoped that it can increase information and knowledge about gout so that people can choose the right solution or management such as consuming pineapple juice to reduce uric acid levels